Inclusion Education Based on the Local Wisdom of the Mask Culture of the Malang to Support Equality in Primary Schools in the Era of Digital Transformation - Faiza, Afidatun; Khoiriya, Rika Mellyaning; Kurnia, Vica Cahya; Laviani, Anggi Via; Rahma, Anggya Zuyyina; Rizqullah, Zeva Khansa Hafizh (Proceedings Series of Educational Studies, 2024)
Inclusion education is an education system that aims to provide equal learning opportunities for all students, regardless of ability, background or physical condition. Inclusive education requires all children, including children with special needs, to learn in the same environment as their peers. In reality, some schools have not fully implemented inclusive education properly and equally. This is due to teachers' difficulties in providing facilities for students with disabilities, teachers' lack of competence in supporting students with special needs, and the lack of utilization of technology as a fun resource and media. This study aims to provide solutions to overcome inequality in inclusive education in primary schools by utilizing the local wisdom of Malang mask culture and the use of technology in the digital era. The method used is qualitative through a literature review of several journals indexed by SINTA and Google Scholar in 2018-2024, and using keywords such as “Inclusive Education,” “Local Wisdom,” “Malang Mask,” “Educational Equality in Elementary Schools,” and “Digital Transformation”. The results show that the implementation of the Local Wisdom of Malang Topeng Culture as a medium to support equality provides many positive benefits in the context of education, especially inclusive education in elementary schools. In addition, this implementation can be improved by utilizing technology in the era of digital transformation to optimize the learning process and create equality in education.